Soft information for source channel coding and decoding - Chugg, K.M.; Demirciler, K.; Ortega, A. (Conference Record of the Thirty-Third Asilomar Conference on Signals, Systems, and Computers (Cat. No.CH37020), 1999)
Soft processing is an effective method used in channel decoding/detection for a system comprising concatenated subsystems. We consider the source-channel coder and the channel-source decoder as such a system and demonstrate how the principles of soft processing can be applied to coding and decoding. This is based on the identification of marginal bit distortion measures associated with the source coder and the channel decoder. We demonstrate how these marginal measures may be used to predict end-te-end distortion and design unequal channel protection (static or dynamic).